2023
DOI: 10.1007/s11292-023-09554-0
|View full text |Cite
|
Sign up to set email alerts
|

If the face fits: predicting future promotions from police cadets’ facial traits

Abstract: Objective: To evaluate the relationship between police cadets' facial traits and their subsequent promotional success.Methods: Using archival police academy photographs, we use a two-phase experiment to evaluate the impact of facial traits on future promotional success. First, respondents (n=507) view randomly selected photographs of cadets (observations=15,669) and evaluate them for facial traits and perceived leadership ability. Second, respondents are presented with random dyads of differentially promoted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Many studies have indicated that humans make social evaluations from facial appearances instantaneously and automatically and facial skin health is a major factor in those evaluations 8,9 . Furthermore, such judgements play an important role in social contexts having identified impact on individual's romantic, economic and career‐related achievements 10,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that humans make social evaluations from facial appearances instantaneously and automatically and facial skin health is a major factor in those evaluations 8,9 . Furthermore, such judgements play an important role in social contexts having identified impact on individual's romantic, economic and career‐related achievements 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Furthermore, such judgements play an important role in social contexts having identified impact on individual's romantic, economic and career-related achievements. 10,11 Eye-tracking studies demonstrated that visual attention to facial skin lesions depends on their anatomical location with two distinct zones of high and low visual attention identified. 12 Acne lesions may be restricted to, or more prevalent in either of visual zones depending on anatomical variant.…”
mentioning
confidence: 99%